Sex determination using cheiloscopy and mandibular canine index as a tool in forensic dentistry - B Bhagyashree; Prakash Gadodia; Abhishek Singh Nayyar; Namrata N Patil; M P Vinod Kumar; Vinita Murgod; Swati S Paraye (Wolters Kluwer Medknow Publications, 2018)
Identification of a person's individuality and sex determination are important for legal as well as identification purposes. The aim of the present study was to check the reliability of cheiloscopy and mandibular canine index (MCI) in the determination of sex in an individual. The aim of this study is to analyze different lip patterns reproduced by the natural dye (vermilion) and lysochrome (Sudan Black II) dyes and to compare the MCI in males and females for the determination of sex and to check the reliability of cheiloscopy and MCI for the same. Latent lip prints were developed using natural dye (vermilion) and lysochrome (Sudan Black II) dyes and their patterns categorized according to Tsuchihashi's classification. MCI were calculated. Analysis of the two was performed. According to discriminant functional analysis, percentage accuracy for cheiloscopy in the determination of sex was found to be 55% while for MCI, the same value was 85%. Natural dye (vermilion) was found as an efficient dye compared to lysochrome (Sudan Black II) dyes for the development of latent lip prints. Both the dyes showed Type I lip print pattern to be common in males and females. Furthermore, all the parameters in MCI were found to be significant in the determination of sex in an individual. The results of the present study revealed MCI to be more reliable in the determination of sex than cheiloscopy.